2018
DOI: 10.1007/s13534-018-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and cytotoxicity of PLA/PCL films

Abstract: Thermodynamically immiscible poly(lactic acid) (PLA) and poly(e-caprolactone) (PCL) were blended and solution-cast by adding the 3% compatibilizer (tributyl citrate, TBC) of the PCL weight. In the PLA/PCL composition range of 99/1-95/ 5 wt%, mechanical properties of the PLA/PCL films with TBC were always superior to those of the films without TBC. The tensile strength of 42.9 ± 3.5 MPa and the elongation at break of 10.3 ± 2.7% were observed for the 93/7 PLA/PCL films without TBC, indicating that PCL addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…Between two formulations, PCL/PVP 95:5 was more resistant; hence, at a greater content of PCL, better mechanical properties can be found in the samples. As reported by Jeong et al [49], PCL addition improved the elasticity of PLA films, as can be observed in Figure 5, PCL/PVP 95:5 sample presented a major elastic range and a higher elastic deformation in comparison with PCL/PVP 85:15 sample.…”
Section: Macro-tensile Measurement On Pcl/pvp Fiber Scaffoldssupporting
confidence: 77%
“…Between two formulations, PCL/PVP 95:5 was more resistant; hence, at a greater content of PCL, better mechanical properties can be found in the samples. As reported by Jeong et al [49], PCL addition improved the elasticity of PLA films, as can be observed in Figure 5, PCL/PVP 95:5 sample presented a major elastic range and a higher elastic deformation in comparison with PCL/PVP 85:15 sample.…”
Section: Macro-tensile Measurement On Pcl/pvp Fiber Scaffoldssupporting
confidence: 77%
“…The specimen with a diameter of 15 mm and a thickness of 5 mm was fabricated and the strength was determined at a point where the specimen thickness decreased by 50%. [5,13] The strength of each sample was tested at least five times.…”
Section: Hydrogel Synthesismentioning
confidence: 99%
“…Detailed experimental procedures are described elsewhere. [4,5,[13][14][15][16][17][18][19][20][21] Cell counting kit-8 (CCK-8, Dojindo Molecular Technologies, Inc., Rockville, MD, USA) is used for the assay of cell proliferation. CCK-8, being nonradioactive, allows sensitive colorimetric assays for the determination of the number of viable cells in cell proliferation.…”
Section: Cytotoxicity and Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations